MicroRNA-4458 suppresses the proliferation of human lung cancer cells in vitro by directly targeting Lin28B - Liu, Chang-hong; Lv, De-sheng; Li, Mo; Sun, Ge; Zhang, Xue-fei; Bai, Yu (Acta pharmacologica Sinica, 2017)
Previous studies have shown that the expression of microRNA-4458 （miR-4458） is dysregulated in hepatocellular carcinoma and colon cancer. In this study, we investigated the direct target of miR-4458 and its biological functions in human lung cancer ceils. By using the database TargetScan, we identified Lin28B, an oncogene, as a direct target gene of miR-4458. In dual-lucJferase reporter assay, we found that miR-4458 mimics dose-dependently inhibited the luciferase activity of the wild-type 3＇UTR of Lin28B in human lung cancer A549 and NCi-H1299 cell lines without affecting its mutant forms, whereas anti-miR-4458, an inhibitor of miR-4458, dose-dependently promoted the luciferase activity of the wild-type 3＇UTR of Lin28B in A549 and NCI-H1299 cell lines without affecting its mutant forms. Overexpression of miR-4458 significantly decreased the protein levels of Lin28B in the cells, and inhibited the cell growth and colony formation. Conversely, knockdown of miR-4458 with anti-miR-4458 significantly increased the protein levels of Lin28B, and promoted the cell proliferation, which could be reverted by knockdown of Lin28B expression. In addition, we detected the expression of Lin28B using RT-PCR in 40 human lung cancer tissues and matched peritumoral tissues, and found that Lin28B was overexpressed in lung cancer tissues and negatively correlated with miR-4458 expression （r=-0.694, P〈0.05）. We conclude that miR-4458 is a tumor suppressor, and Lin28B is the direct target of miR-4458. These results suggest the modulation of miR-4458/Lin28B expression offers a potential therapeutic strategy for lung cancer.